ASUHAN FISIOTERAPI PADA KASUS PIRIFORMIS SYNDROME DENGAN MODALITAS MICROWAVE DIATHERMY ( MWD ) DAN PEMBERIAN TEKNIK STRAIN COUNTERSTRAIN ( SCS ) UNTUK MENGURANGI NYERI - Ismaningsih Ismaningsih; Gading Kurniawan (LPPM Universitas Abdurrab, 2023)
Piriformis syndrome is a peripheral neuritis with pain due to irritation of the piriformis muscle or compression of the upper sciatic nerve. This disorder is also known as wallet syndrome, infrapiriform foramen syndrome, deep gluteal syndrome, or hip socket neuropathy. The Piriformis Syndrome condition presents with symptoms such as pain when there is pressure on the piriformis muscle such as when sitting for too long for 15-20 minutes on a hard surface, pain when performing external rotational and abduction movements of the hip, difficulty with activities such as walking, numbness and tingling in the extremities of the piriformis muscle. The aim of this study is to reduce pain in patients with piriformis syndrome after being given Microwave Diathermy intervention, Strain counterstrain technique 3 times a week for 2 weeks. This research was conducted at Tengku Rafi'an Siak Sri Indrapura Hospital, in March 2023 with a sample of 1 person. The measurement used in this study is a visual analogue scale. Prior to the intervention, the patient obtained a score of 2 for pain on motion, 6.4 for motion pain, 2 for silent pain. After being given the microwave diathermy intervention, the strain counterstrain technique obtained the 6th treatment result on E2: 0 tenderness, 0 silent pain, 3 motion pain .